Curated Topics on Novel Exotic Eco-Friendly Materials for Sustainable Rechargeable Battery Technologies - Kasbe, Arvind; Nazir, Aqsa; Ram, Swetarekha; Sharma, Henu; Sahu, Kisor K (New Environmentally-Friendly Materials, 2025)
This work explores novel and eco-friendly materials that hold transformative potential in addressing the limitations of traditional rechargeable battery systems while aligning with sustainability goals. Beginning with a brief overview of global energy demand and rechargeable battery architectures, this curated study delves into four cutting-edge materials classes, each offering unique advantages. Nanocomposites for Silicon-based anodes represent a breakthrough in enhancing energy density and addressing volume expansion issues, which are the major limitations of silicon anodes. We explore the possibility of recycling silicon from photovoltaic (PV) panels and its associated Life Cycle Assessment (LCA) costs. The study then shifts focus to the realm of two-dimensional (2D) materials, highlighting their exceptional electrical, mechanical, and catalytic properties, which promise substantial improvements in (Li, Na, K-ion based) battery performance. Metal-organic frameworks (MOFs), with their tunable porosity and multifunctionality, are investigated for their role in polysulfide confinement and catalytic enhancement in lithium-sulfur and other battery chemistries. The next topic delves into bio-based catalysts, which have emerged as sustainable alternatives for facilitating electrochemical reactions, leveragin renewable resources to minimize environmental impact. Finally, conductive polymers are briefly considered for their ability to offer flexibility and conductivity, possibility of getting rid of inactive materials in batteries, paving the way for advanced, deformable energy storage devices. This compilation underscores the immense potential of these exotic materials in revolutionizing battery technologies, providing insights into their applications, challenges, and scalability. The discussion concludes with future perspectives on integrating these materials into commercial systems to achieve energy sustainability.